The impact of a computer-based graphic organizer with embedded self-regulated learning strategies on the argumentative writing of students in inclusive cross-curricula settings. (August 2019) - Boykin, Andrea; Evmenova, Anya S.; Regan, Kelley; Mastropieri, Margo
Abstract: This study investigated the effects of a computer-based graphic organizer (CBGO) with embedded self-regulated learning (SRL) strategies on the argumentative writing performance of 4th-and 6th-grade students, including advanced and struggling writers, in the inclusive social studies and science classrooms. This study extended previous research to examine how CBGOs with embedded SRL strategies can support students' writing across content areas. Sixty-nine ( N = 69) students participated in a randomized control trial study. Quantity (e.g., number of words and sentences) and quality (e.g., number of transition words, holistic writing quality) of students' argumentative writing were measured at pretest, posttest, and maintenance test. Results indicated that all students regardless of their abilities and needs benefited from the CBGO with embedded SRL strategies. There were statistically significant differences between the experimental group that used CBGO and the control group that received traditional writing instruction in the quality of writing at posttest and maintenance. There were no statistically significant differences in the quantity measures (e.g., number of words). In addition, the experimental group generalized the improvements in written arguments in the area of social studies to writing in science. These findings add to the limited body of research on computer-based instructional strategies that support all students in writing across the curriculum. Highlights: CBGO with embedded SRL improves the quality of argumentative essays in content areas for 4th-6th grade students. All students were also able to maintain the improvements in writing quality even when the CBGO was removed. All students generalized the improvements from writing an argumentative essay in social studies to writing in science. Students in the experimental group using CBGO outperformed the control condition with traditional writing instruction.